SIKAP MENTAL ENTREPRENEURSHIP WANITA NELAYAN DAN POLA PEMBERDAYAANNYA DI KABUPATEN LOMBOK BARAT - NI MADE WIRASTIKA SARI; MADE SUMA WEDASTRA; I DEWA GEDE SUARTHA; THERESIA SUZANNA CATHARINA (GANEC SWARA, 2018)
As the complexity of life and the burden of the economic burden of the family increases, the duties and roles of women fishermen become increasingly important. Women not only act as housewives but also perform productive activities to increase family income. Limitations faced by fishermen women in the coastal district of West Lombok is the low mental attitude of entrepreneurship, so that their condition is at the level of poverty.This research is a descriptive research, conducted in West Lombok regency with porposive sampling and the number of respondents as much as 75 people determined by non proportional random sampling. Data collection techniques using interview techniques, observation and documentation. The collected data were analyzed descriptively.From the research results can be concluded that: 1). fishermen ladies in the coastal area of West Lombok regency have a moderate attitude of entrepreneurship, this is due to the fact that most of the women are low education fishermen, also fishermen women are very dependent on nature and high risk in facing nature, 2). The activities of women fishermen are still spatial, so there is a need for a joint business group (KUB), and maximizing the government's role, especially the government in facilitating and arranging for the implementation of development or community empowerment to run smoothly, 3). Empowerment should be done through participatory and compressive approaches on economic, sociological, sociocultural and institutional aspects.